Design of Automatic Cooker Hood Using NodeMCU: Rancang Bangun Automatisasi Alat Penghisap Asap Dapur (Cooker Hood) Menggunakan NodeMCU - Budi, Mohamad Istiyo; Saputra, Dwi Hadidjaja Rasjid; Anshory, Izza; Ayuni, Shazana Dhiya (Muhammadiyah University, Sidoarjo, 2024)
Acute respiratory distress syndrome (ARDS) poses a significant health risk due to long-term exposure to carbon monoxide-containing kitchen fumes. Installation of a cooker hood or kitchen smoke extractor with an automated fan is crucial for prevention. This study employed a research and development approach to evaluate the effectiveness of utilizing the NodeMCU ESP8266, MQ-7 sensor, 16x2 I2C LCD, and overall system configuration. Experimental results revealed the MQ-7 sensor's rapid response to smoke intensity changes, with an average 3.77-second response time and a range of detection up to 10cm. Relay testing for fan speed control, using three voltage inputs (5V, 9V, and 12V), categorized conditions as SLOW (PPM>10), MED (PPM <11 & >20), and HIGH (PPM>21). The tests demonstrated optimal performance, as the system successfully adjusted fan speeds based on varying smoke intensity levels, ensuring a healthy air quality environment.